STUDENTS' PERSPECTIVES ON THE USE OF QUIZIZZ AS A GAMIFIED PLATFORM FOR LEARNING ENGLISH SPEAKING - Nawawi, Yosephine Fransiska; Regina, Regina; Riyanti, Dwi (Journal of English Educational Study (JEES), 2024)
This research described students’ perspectives on using Quizizz as a gamified platform for learning English speaking and how they learn through it. It is a descriptive qualitative study. The study subjects were twenty-four Indonesian National Army in Regional Military Command (KODAM) XII Tanjungpura Pontianak personnel. The data were gathered using open-ended questionnaires and semi-structured interviews and analyzed thematically. It showed that Quizizz is a fun platform for learning English speaking. Quizizz positively impacted students’ motivation, assistance, comfort, engagement, and focus during learning. With the support of Quizizz, the students were enthusiastic about learning English speaking more seriously. This gamified platform has increased their self-assurance to speak, competitiveness during learning, and goal awareness. Students are suggested to have an adequate internet connection to do Quizizz with ease and invite their friends to join and explore more English materials available there to gain more challenges in learning through play. The teachers should use the timer feature to reduce students’ ability to look up answers as they work through Quizizz and alert them.